2021
DOI: 10.1016/j.bj.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of bacterial infections in extracellular vesicles release and impact on immune response

Abstract: Extracellular vesicle (EV) biology involves understanding the cellular and molecular mechanisms of cell communication. Studies conducted so far with various bacterial infection models demonstrate the release of various types of EVs that include exosomes and microvesicles. Depending upon the infection and cell type, EV cargo composition changes and ultimately might impact the host immune response and bacterial growth. The mechanisms behind the EVs release, cargo composition, and impact on the immune system have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 79 publications
0
31
0
Order By: Relevance
“…As recently as 2019, several investigators started studying the relationship between metabolism and the immune response at the cellular and organismal levels in infectious diseases and investigating how the pathogen-induced remodeling in the host cell metabolism influences the infectious disease pathogenesis and host physiology ( 85 87 ).…”
Section: Neutrophil Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…As recently as 2019, several investigators started studying the relationship between metabolism and the immune response at the cellular and organismal levels in infectious diseases and investigating how the pathogen-induced remodeling in the host cell metabolism influences the infectious disease pathogenesis and host physiology ( 85 87 ).…”
Section: Neutrophil Biologymentioning
confidence: 99%
“…Studies conducted so far have demonstrated the release of exosomes during extracellular and intracellular bacterial infections. The significance of these cargos in host-pathogen interactions is at a preliminary stage of investigation, and the role of exosomes in host defense and in determining disease outcomes remains unexplored ( 86 , 87 , 105 108 ).…”
Section: Neutrophil Biologymentioning
confidence: 99%
“…Here, Spencer and Yeruva discuss the heterogeneity of extracellular vesicles and their role during bacterial infection [ 16 ]. The authors first provide a detailed description of the diversity of EVs in size, content, and biogenesis pathways.…”
Section: Also In This Issuementioning
confidence: 99%
“…Thereupon, they focus on EV release by cells infected by bacteria, and how this process is both part of the immune response and can be hijacked by pathogens. The review concludes with pertinent open questions regarding the impact of EVs on the inflammatory response and to which degree they benefit the host or the invader [ 16 ].…”
Section: Also In This Issuementioning
confidence: 99%
“…On the other hand, many medium-sized EVs are produced via direct plasma budding as stated above, and therefore are comprised of a lipid bilayer that carries a variety of cell surface proteins and nucleic acids [ 26 ].…”
Section: Introductionmentioning
confidence: 99%